ENHANCING KNOWLEDGE AND EDUCATION OF BONE CANCER FOR ADOLESCENT IN INDONESIA - Abdul Bari, Yunus; Mahyudin, Ferdiansyah; Edward, Mouli; Basuki, Mohammad Hardian; Martanto, Tri Wahyu; Wardhana, Teddy Heri; Suyono, Rifki Effendi; Purnamasari, Yunita; Permana, Muhammad Dimas Arya Candra; Ardana, Fahrizal Novan (Jurnal Layanan Masyarakat (Journal of Public Services), 2025)
Despite much-advanced therapy developed for bone cancer, prevention of the disease remains the most favorable and low-cost management approach. Bone cancer prevention and education should be initiated with adolescents.  Adolescents are the right group to receive bone cancer education, as they are in an active learning phase and have the potential to develop risky behaviors that can increase vulnerability to cancer, as they are in a stage of active learning but also face the development of risky and unhealthy behaviors. This study aims to assess the knowledge of bone cancer among adolescents in Indonesia. It is a cross-sectional study that uses a questionnaire to evaluate the participants' knowledge of bone cancer. A total of 39 questions regarding family history and general knowledge of cancer are given to the students in a pre-test and post-test format. Between the tests, a group of orthopedic specialists provided a short lecture to the students about the basic knowledge and prevention of bone cancer. The study involved 564 students from junior and senior high schools in Indonesia, with an overall mean age of 14.79 years. Bone cancer was mentioned in the family history of only 0.4% of the participants, but 21.5% to 23.5% were unsure about their own family cancer status. The study found a significant statistical result, indicating that the short lectures given by the orthopedic specialists were effective in enhancing the students' knowledge about bone cancer. The findings suggest that adolescents in Indonesia are still uncertain about their family cancer status and often misinformed about the symptoms of bone cancer. However, an educational lecture or discussion led by an expert in the field has proven to be an effective way to improve the students' knowledge about bone cancer.